# maths

posted by .

solve for x given that (1/8)^12x =2^x+3

• maths -

I think you meant

(1/8)^(12x) =2^(x+3)
(2^-3)^(12x) = 2^(x+3)
2^(-36x) = 2^(x+3)
then
-36x = x+3
-37x = 3
x = -3/37

## Similar Questions

1. ### calc

What is dy/dx of y=12/12X-y^3 ???? Any idea anyone?
2. ### math, drbob222

For this problem is it only asking for the exprssion(formula). Or do they want me to solve it. (1) A triangle has sides 3x+7,4x-9,and 5x+6. Find the expression that represents its perimeter. My answer:P=a+b+c I think the question is …
3. ### algebra2

1/3 - 5/6 = 1/X SOLVE 1/3 - 5/6 = 1/X Let's remove the denominators by multiplying by 12X 12X*(1/3) - 12X*(5/6) = 12X*(1/X) Clear the fractions. 4X - 10X = 12 -6X=12 multipy by -1 6X=-12 Divide both sides by 6 6X/6 = -12/6 X = -2 Check …
4. ### help...solving a polynomial....algebra

solve this please....help me....12x(squared)+7x-10 Do you wish to factor this trinomial?
5. ### MATHS!

Kinda lost with this one Given that hx^3 - 12x^2 - x + 3=(2x-1) (2x+1) (x-k) find the values of the constants k and h don't even know where to start start by expanding the right side. then you have hx^3 - 12x^2 - x + 3 = 4x^3 - 4kx^2 …
6. ### Polynomial Fucntion Problem

Could you help me with the following problem, I don't understand how to do it. Am I suppose to use the linear factorization theorem?
7. ### Algebra

To solve 9x^2-12x+4=49 by using the Square Root Property, you would first rewrite the equation was as A. 9x^2-12x-45=0 B.(3x-2)^2=+/-49 C.(3x-2)^2=7 D.(3x^2)^2=49